Nanocomposite magnetic hydrogel with dual anisotropic properties induces osteogenesis through the NOTCH-dependent pathways - Shijia Tang; Yue Yan; Xiaoli Lu; Peng Wang; Xueqin Xu; Ke Hu; Sen Yan; Zhaobin Guo; Xiao Han; Feimin Zhang; Ning Gu (NPG Asia Materials)
Abstract Physical factors in the cellular microenvironment have critical effects on stem cell differentiation. The utilization of physical factors to promote the osteogenic differentiation of stem cells has been established as a new strategy for developing bone tissue engineering scaffolds. In this context, scaffolds with multiscale anisotropy are considered to possess biomimetic properties, which are advantageous for their biological performance. In the present study, a novel magnetic anisotropic hydrogel (MAH) with magnetic and topographic anisotropy was designed by combining static magnetic field-induced magnetic nanomaterials and a hydrogel. In in vitro studies, the MAH exhibited excellent biocompatibility and osteogenic bioactivity. The alkaline phosphatase activity and the expression of osteogenic-related genes and proteins induced by the MAH were greater than those induced by the pure PEGDA–GelMA hydrogel (PGH) and the magnetic isotropic hydrogel (MIH). In addition, the present study revealed that the dual anisotropic properties of the MAH activated the NOTCH1/2 pathway by upregulating SNHG5 and downstream SIRT6, which modulates the level of NOTCH1/2 by antagonizing DNMT1 protein stability, ultimately inducing the osteogenic differentiation of bone marrow mesenchymal stem cells (BMSCs). Furthermore, the MAH, MIH, and PGH were tested for in vivo bone regeneration in rabbits with femur defects, and the results demonstrated that the MAH effectively stimulated bone regeneration. Taken together, these findings suggest that this magnetically and topographically anisotropic biomimetic hydrogel might be a promising candidate for application in the field of bone tissue regeneration.